Drug – Drug Interaction of Dolutegravir and Fluconazole in HIV Patients with Oral Candidiasis – A Literature Review - Fauzia, Rizqi Dinni; Izzah, Zamrotul (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Currently, dolutegravir (with tenofovir and lamivudine or emtricitabine) is the first-line treatment of HIV/AIDS in Indonesia. Considering the 90% prevalence of oral candidiasis as an opportunistic infection in people living with HIV, fluconazole has been used to treat this infection. However, research into the potential for fluconazole drug interactions in people using dolutegravir-based therapy is still limited. Therefore, this study aimed to review published journals of drug-drug interaction between fluconazole and dolutegravir in people living with HIV/AIDS being treated for oral candidiasis. A review was conducted from official journal databases such as PubMed and Google Scholar, only for original studies from 2014 to 2024 with HIV-positive patients were included. Only two out of 313 identified articles met the inclusion criteria. Neither study specifically discussed dolutegravir-fluconazole interaction. Up until now, strong evidence regarding dolutegravir-fluconazole interaction is sufficient. The drug interaction database classified them with no interaction, which was based on a lack of data rather than certain data. Prospective pharmacokinetic studies are required to assess this interaction conclusively and ensure the safety of this common co-administration.